Long-term safety, tolerability, and efficacy of vismodegib in two patients with metastatic basal cell carcinoma and basal cell nevus syndrome - Glen J. Weiss; Raoul Tibes; Lisa Blaydorn; Gayle Jameson; Molly Downhour; Erica White; Ivor Caro; Daniel D. Von Hoff (PAGEPress Publications, 2011)
Tumor responses in advanced basal cell carcinoma (BCC) have been observed in clinical trials with vismodegib, a SMO antagonist. The result of SMO antagonism is inhibition Hedgehog Signaling Pathway (HHSP) downstream target genes. HHSP inhibition has been shown to affect stem cells responsible for blood, mammary, and neural development. We report on our experience of treating two patients with advanced BCC participating. These two patients have had no new BCCs develop for at least 2.25 years. Both patients have been receiving ongoing daily treatment with vismodegib for greater than 2.75 years without experiencing any significant side effects. After prolonged continuous daily dosing with a SMO antagonist, we have not observed a significant alteration in hematologic parameters or physical abnormalities of the pectoral regions of two patients with advanced BCC.